METTL3 obstructs vascular smooth muscle cells osteogenic reprogramming by methylating Runx2 in chronic kidney disease - Meijuan Cheng; Jingjing Jin; Dongxue Zhang; Mei Xiao; Hairong Zhao; Xiaoying Zhao; Shenglei Zhang; Yaling Bai; Jinsheng Xu (Communications Biology)
Abstract The reprogrammed osteogenic phenotype of vascular smooth muscle cells (VSMCs) is considered a critical mechanism of vascular calcification (VC) in chronic kidney disease (CKD). Currently, the RNA N6-methyladenosine (m6A) modification is deciphered to be dynamically and reversibly participated in functional regulation of VSMCs. Here, we discover that serum m6A levels in RNA are dramatically reduced as VC progressed in patients with CKD, and this m6A demethylation is mainly due to the downregulation of methyltransferaselike-3 (METTL3). Functionally, METTL3 depletion exacerbates, whereas its overexpression attenuates calcification progression and osteogenic reprogramming. Mechanistically, Runx2, a crucial osteogenic gene, is identified as a key downstream target of METTL3-mediated m6A methylation. METTL3 negatively regulates Runx2 expression through the m6A modification. Overexpression of METTL3 exacerbates Runx2 mRNA degradation, which is orchestrated by the m6A reader YT521-B homology domain family 2 (YTHDF2) through specifically recognizing its m6A sites in the 3′UTR region. Finally, in vivo METTLs inhibitor SAH treatment aggravates VC and osteogenic conversion in aortas of CKD rats, accompanied by Runx2 expression upregulation. These above data reveal an underlying mechanism by which the m6A writer METTL3 regulates Runx2 expression through YTHDF2-mediated mRNA degradation and suggest a potential therapeutic strategy to reverse the osteogenic reprogramming of VSMCs.